Educação e democracia: um estudo comparado entre o pensamento de Paschoal Lemme (1904-1997) e o de Anísio Teixeira (1900-1971) - MOURA, Adriana Dias de (Universidade Federal do Pará, 2017)
This dissertation study aims to focus on the relationship between education and democracy at the thought of Paschoal Lemme (1904-1997) and Anísio Teixeira (1900-1971). The problem and the issues that guided the research, respectively, were: What relations are possible grasp of the concepts that Paschoal Lemme and Anísio Teixeira historically built by linking education and democracy? What is the intellectual itinerary and life of the authors? What theoretical bases underlied the thought of Paschoal Lemme and Teixeira to articulate education and democracy? What is the relationship established between education and democracy at the thought of each author? What similarities and differences exist in the thought of Paschoal Lemme and Anísio Teixeira in the relationship between education and democracy? The general objective was to analyze, through the Cultural History and Comparative Study of intellectual thought, possible relations between the conceptions of Paschoal Lemme and Anísio Teixeira on education and democracy, identifying congruence and differences. And the specific ones: Reconstitute the itinerary and intellectual life of each author; Describe the theoretical basis underlying the thinking of the authors; Rebuild relations which the authors established between education and democracy; Infer results from the points of divergence and convergence in the thinking of authors when dealing in their works the relationship between education and democracy. Methodologically, it is a bibliographical and documentary type of search, located within the area of History of Education, with basis in Comparative History, New Cultural History and Intellectual History. The objects of analysis were the books "Educação Democrática e Progressista (1961)" and "Educação na URSS (1955)" by Paschoal Lemme. The other books were "Educação no Brasil (1969)" and "Em marcha para democracia: à margem dos Estados Unidos (1934)" by Anísio Teixeira, as well as correspondence. Paschoal Lemme and Anísio Teixeira stood out for his work in Brazilian public education in the twentieth century. Paschoal Lemme and Anísio Teixeira saw education as a social process and the school as a fundamental institution for the development of individual potential of every being. However, Anísio Teixeira believed in the democratization of education as a potential factor to transformate the society, while Paschoal Lemme argued that the democratization of society pervaded by changing the economic and political system so as to democratize education. Some of the points of convergence between Anísio Teixeira and Paschoal Lemme are: They acted together in ABE; They defended the right to a public, secular and democratic education; both of them had the spirit of freedom and humanity. The greatest thought divergence of both is related to the ideal of democracy, while Paschoal Lemme was socialist, Teixeira was a liberal-pragmatic.